Space and rituality in lima in the 18th century: A Baroque religious festival in the Alameda de los Descalzos - Negro Tua, Sandra (2007)
This study uncovers the origins of a popular religious festival of reparation for a Eucharistic desecration, celebrated annually to this day, and reveals the peculiarities of public devotion in the various social strata of Lima in the 18th century.